Brain perfusion SPECT can differentiate clinical subtypes of Parkinson's diseases. Issue 3 (16th August 2013) - Song, In‐Uk; Chung, Yong‐An; Huh, Ryoong
ABSTRACT The clinical heterogeneity of Parkinson's disease (PD) is well recognized. It is possible to distinguish two main clinical subgroups, a tremor dominant PD (TP) and nontremor dominant PD (NTP). However studies compared the regional cerebral blood flow between subtypes of PD had rarely been performed yet, although the classification of subtypes was very important because of difference of disease progression and prognosis between subtypes of PD. We recruited 43 patients with PD (21 TP and 22 NTP). All patients with PD underwent brain perfusion SPECT and evaluated motor severity by using the Hoehn and Yahr stage and Part III of the unified Parkinson's disease rating scale (UPDRS). We also compared tremor and nontremor symptoms with motor phenotype scores between two subtypes of PD. Brain perfusion SPECT showed significant hypoperfusion in TP compared with NTP in the left occipital lobe and middle occipital gyrus, left frontal lobe and superior frontal gyrus, cerebellar hemisphere, left lentiform nucleus. On the other hand, brain perfusion SPECT of NTP compared with TP showed hypoperfusion in right parietal lobe and precuneus, left temporal lobe and inferior temporal gyrus, both frontal lobe and inferior frontal gyrus. The present study indicates that pathophysiology of TP compared to NTP has more closely association with neuronal circuits including cerebellar pathway, such as CTC circuit. Therefore, we cautiously assert that neuronal systems other than the nigrostriatal dopaminergic system are likely involved in the generation of tremor in PD. © 2013 Wiley Periodicals, Inc. Int J Imaging Syst Technol, 23, 222–226, 2013